Teacher-Directed Collaborative Action Research as a Mediating Tool for Professional Learning in Rural Contexts - Skyhar, Candy (Australian and International Journal of Rural Education, 2021)
Through a single-case study design, the research study described in this article examined one rural Canadian school division's use of teacher-directed collaborative action research as a mediating tool for teacher learning within a professional development (PD) initiative known as the Numeracy Cohort. The PD initiative brought together a dozen K-12 teachers from across a very small (but geographically distanced) school division in Manitoba, Canada. In addition to learning about several strategies for teaching mathematics and improving student numeracy skills, the teachers in the Numeracy Cohort engaged in collaborative action research projects, designing materials and implementing new strategies in their unique, often multi-grade, rural classrooms. In addition to the changes and improvements noticed by teachers through their collaborative action research, findings from the study illustrated several strengths of teacher-directed collaborative action research, including the autonomy it afforded teachers to engage in work directly related to their classroom contexts, its ability to foster collaboration between colleagues, and its ability to build connections across schools within a diverse rural context. Findings from the study also suggested that consideration should be given to both ways of supporting the action research process, and the complexities of leadership in rural settings if teacher-directed collaborative action research is to be used as a mediating tool for learning.